Obesity and methotrexate treatment failure in rheumatoid arthritis patients in Cipto Mangunkusumo Hospital, Indonesia - Fauzia, Fara; Adnan Prihartono, Nurhayati; C. Adisasmita, Asri; Umi Partan, Radiyati; Djuwita Hatma, Ratna; Hidayat, Rudy (International Journal of Public Health Science (IJPHS), 2024)
Rheumatoid arthritis (RA) is a chronic, systemic autoimmune disease which mainly manifests in the joints. Methotrexate (MTX) is a widely used pharmacological treatment for RA. To date, no prior research has investigated the effect of obesity on MTX treatment outcomes among RA patients in Indonesia. This research aimed to investigate the effect of obesity on MTX monotherapy failure in RA patients. We conducted a retrospective cohort study using medical records from the Rheumatology Clinic at Cipto Mangunkusumo Hospital from March 2017 to December 2021. Descriptive and estimation analyses were performed to assess the sample characteristics based on each variable and a logistic regression analysis was conducted to evaluate the association between obesity and MTX treatment failure. Out of 72 subjects, the proportion of MTX treatment failure was 57.1% (20/35) among obese patients and 37.8% (14/37) among non-obese patients. Obese subjects exhibited a 2.11-fold increased risk of MTX treatment failure compared to non-obese patients (OR 2.11; 95% CI 0.81-5.45). The number of joints involved was found to emerge as a confounding factor in this study. Our findings suggest that RA patients with obesity potentially have an increased risk of MTX treatment failure compared to non-obese RA patients.